Primary sinonasal mucosal melanoma – a diagnostic and histological conundrum - Bakrin, Ikmal Hisyam; Liew, Kong Yew; Mahayidin, Hasni; Abu Hasan, Hasyma; Doi, Mohamad (Ministry of Health, Brunei Darussalam, 2017)
Primary sinonasal mucosal melanomas (PSMM), a rare subtype of melanomas offers significant diagnostic challenge clinically and histologically especially when amelanotic, as they can show many histologic mimics that require immunohistochemical and molecular studies to confirm the diagnosis. We report the case of a 50-year-old male presented with persistent left nasal blockage and epistaxis secondary to a fleshy and friable lobulated mass occupying the left nasal cavity and nasopharynx. The tumour was excised endoscopically and histology confirmed a malignant tumour consisting of small round blue cells with hyperchromatic nuclei, in solid sheets with areas of angiocentric pattern (H & E staining). The cells were positive for S100 protein and focally positive for HMB-45 and Melan A and a diagnosis of PSMM was made. However, he defaulted the subsequent radiotherapy and presented back a few months later with tumour recurrence locally and nodes metastasis. Despite undergoing radiotherapy, he died after two cycles due to an episode of acute coronary syndrome.